Magnetically activated electroactive microenvironments for skeletal muscle tissue regeneration - Ribeiro, Sylvie Oliveira (2020)
This work reports on magnetoelectric biomaterials suitable for effective proliferation and differentiation of myoblast in a biomimetic microenvironment providing the electromechanical stimuli associated with this tissue in the human body. Magnetoelectric films are obtained by solvent casting through the combination of a piezoelectric polymer, poly(vinylidene fluoride-trifluoro-ethylene), and magnetostrictive particles (CoFe2O4). The nonpoled and poled (with negative and positive surface charge) magnetoelectric composites are used to investigate their influence on C2C12 myoblast adhesion, proliferation, and differentiation. It is demonstrated that the proliferation and differentiation of the cells are enhanced by the application of mechanical and/or electrical stimulation, with higher values of maturation index under mechanoelectrical stimuli. These results show that magnetoelectric cell stimulation is a full potential approach for skeletal muscle tissue engineering applications